Motives behind the mobility of university graduates - A study of three German universities - Sidonia von Proff; Matthias Duschl; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2014)
The mobility of university graduates is influenced by economic factors and individual attitudes. The paper at hand focuses on individual characteristics influencing the spatial preferences of graduates from three universities in Hesse (Germany). Using survey data from prospective graduates in 2012 we find that the majority has preferred locations during the job search, which are on average farther away if the respondents focus on broad availability of job opportunities and leisure/cultural activities. Social ties and a focus on good infrastructure leads to a search dominantly at familiar places, i.e. the home or university region.
Keywords: J61; I23; 330; graduate mobility; regional labor mobility; universities